The effect of a varying pyridine ligand on the anticancer activity of Diiron(I) bis-cyclopentadienyl complexes - Rossi, Annachiara; Biancalana, Lorenzo; Vančo, Ján; Malina, Tomáš; Zacchini, Stefano; Dvořák, Zdeněk; Trávníček, Zdeněk; Marchetti, Fabio (Chemico-biological interactions, 2025)
The new diiron complexes [Fe2Cp2(CO)(L)(μ-CO){μ-CN(Me)(Cy)}]CF3SO3 (L = pyridine, 3a; 4-aminopyridine, 3b; 4-dimethylaminopyridine, 3c; 4-trifluoromethylpyridine, 3d; nicotinic acid, 4; Cp = η5-C5H5, Cy = C6H11 = cyclohexyl) were synthesized in moderate to high yields using two distinct synthetic routes from the precursors 1 (L = CO, for 4) and 2 (L = NCMe, for 3a-d), respectively. All products were characterized by IR and multinuclear NMR spectroscopy, and the structures of 3b and 3d were ascertained by X-ray diffraction studies. The behavior of the complexes in aqueous solutions (solubility, Log Pow, stability) was assessed using NMR and UV-Vis methods. The in vitro antiproliferative activity of 3a-c and 4 was evaluated against seven human cancer cell lines (A2780, A2780R, A549, MCF-7, PC3, HOS and HT-29) and one normal cell line (MRC-5), following 24 h of incubation (MTT test). Overall, 3-4 demonstrated stronger cytotoxicity than cisplatin, with 3c emerging as the most potent compound. The activity seems primarily linked to the inhibition of metabolic processes in the cancer cells, including depletion of reactive oxygen species (ROS) levels. However, subtle differences have been observed between the complexes, with 4 exerting its cytotoxicity through a distinct multimodal mechanism.
Keywords: Ligands; Drug Screening Assays, Antitumor; Humans; ligandy; Metals in medicine; komplexní sloučeniny; Diiron complexes; In vitro cytotoxicity; Antineoplastic Agents; krystalografie rentgenová; Crystallography, X-Ray; lidé; proliferace buněk; Coordination Complexes; Pyridines; Cellular effects; Pyridine ligand; Cell Proliferation; pyridiny; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; Cell Line, Tumor; Bioorganometallic chemistry